2019
DOI: 10.1111/jscm.12189
|View full text |Cite
|
Sign up to set email alerts
|

Ramp Up and Ramp Down Dynamics in Digital Services

Abstract: Volume ramp ups are notoriously difficult in digital services, where market pressures can lead to ramping up too soon and too rapidly which in turn can lead to the need to ramp down. This paper addresses the challenge of taking innovation to scale in an established firm by enhancing our understanding of the nature of service ramp ups and ramp downs. Digital service ramp ups differ substantially from production ramp ups as the speed is much greater, and problems are visible to customers. However there are simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…Finally, our study brings to the fore the importance of supply chain attributes when innovating to capture a situational and temporal market‐wide opportunity. Consistent with previous studies on flexible supply chain, we show that supply chains play an important role in a competitive landscape where urgency becomes imperative (Akkermans et al, 2019). Extending previous studies on the role of supply chains in delivering innovation involving suppliers' innovative capabilities, joint buyer–supplier product development, and the like, our analysis highlights the salient role of resource congestion in the digital supply chain in delivering opportunistic innovation (Aggarwal, 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, our study brings to the fore the importance of supply chain attributes when innovating to capture a situational and temporal market‐wide opportunity. Consistent with previous studies on flexible supply chain, we show that supply chains play an important role in a competitive landscape where urgency becomes imperative (Akkermans et al, 2019). Extending previous studies on the role of supply chains in delivering innovation involving suppliers' innovative capabilities, joint buyer–supplier product development, and the like, our analysis highlights the salient role of resource congestion in the digital supply chain in delivering opportunistic innovation (Aggarwal, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Creating and capturing value in the digital business environment is becoming increasingly competitive (Evans, 2015; Fisher et al, 2018; Moon et al, 2018). Modern digital infrastructure enables fast changes in both the demand and supply of goods and services (Akkermans et al, 2019; Pervin et al, 2019). Thus, firms in digital environments must grapple with consumers' constantly changing requirements for their product and service offerings (Downes & Nunes, 2018; Fisher et al, 2018; Moon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For manufacturing companies, Bergs et al [6] underline that product lifetime tends to decrease with a more rapid evolution of customer requirements. This is also true for service companies, as Akkermans et al [5] explain in their research about ramp-up and ramp-down dynamics. Indeed, it is shown that market pressures lead to accelerate the design of new services and their deployment.…”
Section: Introductionmentioning
confidence: 80%
“…Companies are increasingly confronted with issues during ramp-up of products and services, which is partly due to growing market pressure [5]. For manufacturing companies, Bergs et al [6] underline that product lifetime tends to decrease with a more rapid evolution of customer requirements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation